The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13024-021-00425-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolic profiling of Parkinson’s disease by liquid chromatography-mass spectrometry

Abstract: Background Parkinson’s disease (PD) is a prevalent neurological disease in the elderly with increasing morbidity and mortality. Despite enormous efforts, rapid and accurate diagnosis of PD is still compromised. Metabolomics defines the final readout of genome-environment interactions through the analysis of the entire metabolic profile in biological matrices. Recently, unbiased metabolic profiling of human sample has been initiated to identify novel PD metabolic biomarkers and dysfunctional met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 82 publications
10
111
4
Order By: Relevance
“…6 b, empty bars). These observations were in line with the clinical studies showing reduced fatty acid metabolism in plasma from patients with PD [ 40 ]. In addition, peroxisome proliferator-activated receptor (PPAR) signaling pathway, a lipid sensor [ 41 ], was consistently elevated in mutation-corrected iPSCs.…”
Section: Resultssupporting
confidence: 90%
“…6 b, empty bars). These observations were in line with the clinical studies showing reduced fatty acid metabolism in plasma from patients with PD [ 40 ]. In addition, peroxisome proliferator-activated receptor (PPAR) signaling pathway, a lipid sensor [ 41 ], was consistently elevated in mutation-corrected iPSCs.…”
Section: Resultssupporting
confidence: 90%
“…Both glutamate and glycine are neurotransmitters. Although that is not the case in our data, proline has been reported previously as being overrepresented in PD 24 and is known to be linked to protein metabolism and structure, cell differentiation, conceptus growth and development 39 , and gut microbiota community reequilibration in cases of dysbiosis, with L-proline dietary supplementation being known to affect gut microbial composition and gut concentrations of several bacterial metabolites 40 .…”
Section: Correlations Between Bacterial Taxa and Metabolites Featurescontrasting
confidence: 70%
“…If methylation capacity is compromised due to an alteration in folate metabolism, there may be impaired phosphatidylcholine synthesis along with shunted or disrupted carnitine shuttle observed in our results. Altered carnitine metabolism, fatty acids, and steroid metabolism was also observed in a metabolomics profiling study recently reported 24 . Several studies have reported decreased levels of carnitine and acylcarnitines in plasma from PD patients 21,25,26 ; however, according to Jiménez-Jiménez et al (1997) 27 no changes were observed in acylcarnitine levels in plasma or cerebrospinal fluids of PD participants.…”
Section: Serum Metabolomementioning
confidence: 58%
“…Phenylacetylglutamine, another gut microbial metabolite, has been reported to correlate with chronic kidney disease, diabetes mellitus, cardiovascular disease, and Parkinson's disease (Poesen et al, 2016;Urpi-Sarda et al, 2019;Shao et al, 2021 cardiovascular disease risks in a large sample clinical study (Nemet et al, 2020). This study suggested a clinical association between elevated PAGln levels and the overall burden of WMH and P-WMH.…”
Section: Discussionmentioning
confidence: 63%